Super why : three little pigs. (Calif. : Out of the Blue Enterprises, 2011)
Jill keeps knocking down Pig's tower and he wants her to stop. Super why and his friends fly into the three little pigs story and come face to face with the Big Bad Wolf himself. After all, he knows a thing or two about knocking things down. When all the huffling and puffing dies down. Pig learns an important lesson about friendship.